STUDY OF VITAMIN-D STATUS AND INSULIN RESISTANCE IN OBESE ADOLESCENTS - DR. MEERA SHIVASHEKAR; DR. M. VASANTHA; SARGURU. D (International Journal of Pharma and Bio Sciences, 2016)
Vitamin D deficiency is a pandemic health problem and a risk factor for the development of impaired glucose tolerance in childhood obesity. The aim of the study is to determine the relationship between 25- hydroxy vitamin-D levels and insulin resistance in obese and non obese patients. The study group included 50 obese and 50 non obese adolescents aged 16-18 years. Anthropometric data were collected and fasting serum glucose, insulin and 25-(OH) D was measured. The homeostatic model assessment of insulin resistance was calculated in both groups. The levels of 25-(OH) D in obese group were significantly lower and (p <0.001) HOMA-IR were significantly higher than non obese adolescents (p<0.001). The mean fasting insulin levels in obese adolescents were found to be lower than non obese adolescents. In the obese group vitamin D and insulin showed a positive correlation with insulin resistance. The finding suggests that insulin resistance plays a major role in obesity than vitamin D levels.